2015
DOI: 10.1016/j.applthermaleng.2015.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Boltzmann simulation of convection melting in complex heat storage systems filled with phase change materials

Abstract: A double-population lattice Boltzmann method is applied to simulate the convectiondiffusion phenomena associated with solid-liquid phase transition processes. The research focus is the lattice Boltzmann method advanced to complex multitube heat storage system with different numbers and arrangements of tubes. A systematic comparison of different lattice Boltzmann models for thermal and flow field in the phase-change process is numerically conducted in a square cavity; the numerical results are validated by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(28 citation statements)
references
References 43 publications
3
25
0
Order By: Relevance
“…The lattice Boltzmann method is relatively new compared to the classical approaches based on the Navier-Stokes equations. This technique has been used with a great success to simulate different physical behaviors of magnetohydrodynamic fluids [1,2], inhomogeneous mediums [3,4], phase change materials [5,6], flows with chemical reactions [7], and porous media [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The lattice Boltzmann method is relatively new compared to the classical approaches based on the Navier-Stokes equations. This technique has been used with a great success to simulate different physical behaviors of magnetohydrodynamic fluids [1,2], inhomogeneous mediums [3,4], phase change materials [5,6], flows with chemical reactions [7], and porous media [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the existing thermal LB models for solid-liquid phase change can be generally classified into two major categories: the phase-field method [221][222][223][224][225][226][227][228] and the enthalpy-based method [54][55][56][57][58][75][76][77][78][79][80][81]194,[229][230][231][232][233][234][235][236][237][238][239][240][241][242][243][244][245][246]. Besides, a couple of LB models were recently developed based on some interface-tracking methods [180,247].…”
Section: The Lb Methods For Solid-liquid Phase-change Heat Transfermentioning
confidence: 99%
“…The liquid fraction l f is determined by Eq. In a recent study carried out by Luo et al [238], different enthalpy-based LB models for solid-liquid phase change have been tested and analyzed. They found that the HLBM-MRT scheme (i.e., MRT-LB model [110] for flow field, and enthalpy-based LB model [236] for temperature field) is more suitable for modeling convection dominated melting process.…”
Section: The Enthalpy-based Lb Modelsmentioning
confidence: 99%
“…It was noticed that with an increase in number of HTF tubes from 1 to 4, the melting time was reduced by 29%. Likewise, Luo et al [26] numerically examined the effect of HTF tubes number and their orientations in horizontal shell-and-tube heat exchanger on thermal performance. It was noticed that melting time for single HTF tube was 5 times as compared to nine HTF tubes case.…”
Section: Introductionmentioning
confidence: 99%